Biomedical engineering :Bridging medicine and technology - Saltzman, W. Mark (united kingdom Cambridge university press, 2015)
"The second edition of this popular introductory undergraduate textbook uses examples, applications, and profiles of biomedical engineers to show students the relevance of the theory and how it can be used to solve real problems in human medicine. The essential molecular biology, cellular biology, and human physiology background is included for students to understand the context in which biomedical engineers work. Updates throughout highlight important advances made over recent years, including iPS cells, microRNA, nanomedicine, imaging technology, biosensors, and drug delivery systems, giving students a modern description of the various subfields of biomedical engineering. Over 200 quantitative and qualitative exercises, many new to this edition, help consolidate learning, whilst a solutions manual, password-protected for instructors, is available online. Finally, students can enjoy an expanded set of leader profiles in biomedical engineering within the book, showcasing the broad range of career paths open to students who make biomedical engineering their calling"--
Machine generated contents note: 1. Introduction: what is biomedical engineering?; Part I. Molecular and Cellular Principles: 2. Biomolecular principles; 3. Biomolecular principles: nucleic acids; 4. Biomolecular principles: proteins; 5. Cellular principles; Part II. Physiological Principles: 6. Communication systems in the body; 7. Engineering balances: respiration and digestion; 8. Circulation; 9. Removal of molecules from the body; Part III. Biomedical Engineering: 10. Biomechanics; 11. Bioinstrumentation; 12. Bioimaging; 13. Biomolecular engineering I: biotechnology; 14. Biomolecular engineering II: engineering of immunity; 15. Biomaterials and artificial organs; 16. Biomedical engineering and cancer.
Keywords: Biomedical Engineering